Quranic Printing Issues in Malaysia: An Examine at Ministry of Home Affairs - Ahmad , Mohd Hasbie al-Shiddieque; Mohamad, Khairul Anuar; Mohamad, Khairul Anuar (International Journal of Psychosocial Rehabilitation, 2020)
Quranic printing has gone through a few modifications, in parallel with the printing’s revolution. The first printed al-Quran was in the year 1530 AD in Venice, Italy. Ever since, several countries took the opportunity to print the al-Quran including Germany, Russia, Iran, India, and Turkey. Nevertheless, the Quranic printing requires strict supervision to ensure the authenticity of al-Quran, which led to some countries like Saudi Arabia, Egypt, and Jordan taking the initiative to establish the Quranic Tasheh Committee to supervise all activities relating to Quranic printing in the country. This research focuses on the issues of Quranic printing in Malaysia and makes the Ministry of Home Affairs of Malaysia (MOHA) as an observation place. This research is a qualitative study and chooses research methods of interview and document analysis as the research instruments. Results found that the Quranic Text Control Unit of MOHA has introduced three main steps to ensure that the Quranic text is free from any errors namely mistakes detected in the Muṣḥaf al-Quran, validation of approval code, and hologram stickers.